Productivity Growth and Firm Ownership: An Analytical and Empirical Investigation - Ehrlich, Isaac; Gallais-Hamonno, Georges; Liu, Zhiqiang; Lutter, Randall (Journal of Political Economy, 1994)
We focus on the effect of state versus private ownership on the rates of firm-specific productivity growth and cost decline by developing a model of endogenous, firm-specific productivity growth and testing its implications against panel data on 23 international airlines of varying levels of state ownership over the period 1973-83. Our model and empirical results show that state ownership can lower the long-run annual rate of productivity growth or cost decline, but not necessarily their levels in the short run. Observed level differences in productive efficiency across private and state-owned firms may thus be a function of the age distribution of the firms being compared. These results appear to be independent of whether the firms operate under apparently more or less competitive or regulated markets and whether they differ in production scales. The analysis offers new insights concerning the recent trend toward privatizing state-owned enterprises that has been observed in many countries.